2012
DOI: 10.3109/00365521.2012.725092
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine in patients with inflammatory bowel disease: results of a cross-sectional study in Norway

Abstract: Use of CAM was common among IBD patients attending outpatient clinics. Both demographic and clinical factors were associated to CAM use, but the factors differed in their significance for UC and CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 41 publications
2
36
1
Order By: Relevance
“…Gender differences are commonly reported in previous studies of CAM use, both in general populations and in IBD populations [1,10,12,14,15]. Additionally, those who were married reported higher CAM use compared to unmarried.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Gender differences are commonly reported in previous studies of CAM use, both in general populations and in IBD populations [1,10,12,14,15]. Additionally, those who were married reported higher CAM use compared to unmarried.…”
Section: Discussionmentioning
confidence: 68%
“…Hildsen et al [7] reported somewhat varying use of acupuncture among IBD patients, from 13% to 38% [7]. In a Norwegian study of IBD outpatients, acupuncture was the most frequently used CAM (20% of the CAM users) [12]. The Slovak acupuncture society is sectioned within the Slovak Medical Society (SLS), and has been included as a specialized medical field for medical doctors since 1990 [13].…”
Section: Discussionmentioning
confidence: 99%
“…The patient group with Crohn disease (CD) scores significantly lower on the general health and vitality dimensions after 10-year follow-up 11. The use of complementary and alternative medicine (CAM) was common among IBD patients attending outpatient clinics in Norway 12. Patients with IBD found it easier to communicate about CAM with the IBD nurses than with physicians, and dietary change was one important CAM treatment 13…”
mentioning
confidence: 99%
“…Thirty to fifty per cent of people suffering from this have tried some form of alternative or complementary medicine, maybe due to the side effects and/or lack of effectiveness of the conventional therapies (Opheim, Bernklev, Fagermoen, Cvancarova, & Moum, 2012). However, these treatments are not generally regulated by the official agencies for the evaluation of medicinal products, and manufacturers can claim them safe and effective, without proving it.…”
Section: Resultsmentioning
confidence: 99%